Influence of socioeconomic status on the association between low weight at birth and stunted growth or overweight in rural and urban Indonesian prepubertal children - Madarina Julia; M. M. van Weissenbruch; H. A. Delemarre-van de Waal; Achmad Surjono (Indonesian Pediatric Society, 2008)
Background Low birth weight (LBW) has been associated with in-creased risk for both stunted growth andand overweight later in life.Objective To assess relative contribution of LBW on the preva-lence of stunted growth or overweight in rural and urban Indo-nesian children in Indonesia.Methods This is a cross-sectional survey of 2 833 (1125 rural and1708 urban) school-aged prepubertal children. Each child had dataon age, sex, stature, BMI (body mass index) and birth weight.Results Compared to the urban population, the prevalence ofstunted growth was significantly higher in the rural, i.e. 16.3 vs.32.7%, P<O.OOl. However, there was no significant difference iinn the prevalence of LBW in the two communities. While overall,stunted children were more likely to be born with LBW, OR 1.80(95%CI 1.31; 2.47), P<O.OOl. After stratifying data into rural andurban residences, the contribution of LBW on the risk of stuntedgrowth appeared to be only significant in the urban population, OR2.42 (95%CI 1.59; 3.68), P<O.OOl. In the rural, similar proportionsof LBW were found in stunted and not stunted children. Test of in-teraction showed that this difference in OR was significant, the ratioof OR 1.88 (95%CI 1.11; 3.17), P=0.02. We observed no associationbetween LBW and overweight.Conclusions In rural area, LBW is not an important contributorfor stunted growth, while in urbanarea LBW is an important riskfactor for stunted growth. As there is no significant difference inthe prevalence of LBW between the two communities, the dif-ference in the prevalence of stunted growth is more likely to beassociated with different pattern of post-natal growth